STUDENT'S ABILITY IN WRITING DESCRIPTIVE TEXT AT ELEVENTH CLASS OF TATA BUSANA AT SMK PANGERAN ANTASARI - Litnawati Br Tarigan Tua; Eben Gunawan Naiborhu; Fachri Yunanda; Bambang Nur Alamsyah Lubis (English Language Teaching Prima Journal (ELT), 2024)
In writing descriptive text, there are five aspects that need to be considered: identification, description, language use, vocabulary, and mechanics. Based on the problems identified at the beginning of the research, the aim of this research is to assess students’ ability to write descriptive text was determine students' abilities in writing descriptive texts for class XI students at SMK PANGERAN ANTASARI. This research focuses on 23 students. Researchers apply qualitative methods. This research was carried out directly on Tuesday, May 21 in class XI of SMK PANGERAN ANTASARI. Researchers examined deficiencies in students' descriptive text writing. This research focuses on categorizing students' writing errors. Data was obtained through a descriptive text-writing test. The results of the research show that students’ abilities in writing identification varied from bad to good, their ability in writing descriptions was less than satisfactory, their ability in using language, vocabulary and mechanics was also less than satisfactory. Additionally the research shows that students experience struggles in clearly identifying objects, developing ideas related to their lack of understanding of the structure of the simple present tense, as well as facing limitations in vocabulary and making mechanical mistakes.